A study to evaluate the effectiveness of Best Beginnings' Baby Buddy phone app in England: a protocol paper. (23rd July 2019) - Deave, Toity; Kendal, Sally; Lingam, Raghu; Day, Crispin; Goodenough, Trudy; Bailey, Elizabeth; Ginja, Sam; Nightingale, Sam; Coad, Jane
Abstract: Introduction: Developments in information and communication technologies have enabled electronic health and seen a huge expansion over the last decade. This has increased the possibility of self-management of health issues. Purpose: To assess the effectiveness of the Baby Buddy app on maternal self-efficacy and mental well-being three months post-birth in a sample of mothers recruited antenatally. In addition, to explore when, why and how mothers use the app and consider any benefits the app may offer them in relation to their parenting, health, relationships or communication with their child, friends, family members or health professionals. Methods: We will use a mixed-methods approach, a cohort study, a qualitative element and analysis of in-app data. Participants will be first-time pregnant women, aged 16 years and over, between 12 and 16 weeks of gestation and recruited from five English study sites. Evaluation plan: We will compare maternal self-efficacy and mental health at three months post-delivery in mothers who have downloaded the Baby Buddy app compared with those that have not downloaded the app, controlling for confounding factors. Women will be recruited antenatally between 12 and 16 weeks of gestation. Further follow-ups will take place at 35 weeks of gestation and three months post-birth. Data from the cohort study will be supplemented by in-app data that will include, for example, patterns of usage. Qualitative data will assess the impact of the app on the lives of pregnant women and health professionals using both focus groups and interviews. Ethics: Approval from the West Midlands-South Birmingham Research Ethics Committee (NRES) (16/WM/0029) and the University of the West of England, Bristol, Research Ethics Committee (HAS.16.08.001). Dissemination: Findings of the study will be published in peer reviewed and professional journals, presented locally, nationally and at international conferences. Participants will receive a summary of the findings and the results will be published on Best Beginnings' website.